PERANCANGAN UI/UX SISTEM MANAJEMEN ARSIP DOKUMEN DIGITAL PADA PT. BANK XYZ - Ramadhona Ramadhona; Kiky Rizky Nova Wardani (LPPM Politeknik Pratama Kendal, 2026)
Document archive management in the banking sector requires high levels of efficiency, accuracy, and security. However, at PT Bank XYZ, the archiving process is still conducted manually, leading to several issues such as delays in document retrieval, risk of document loss, data duplication, and limited physical storage space. This study aims to design the user interface (UI) and user experience (UX) of a digital document archive management system that aligns with user needs and actual workflows in a banking environment. The research employs the Design Thinking method, which consists of five stages: empathize, define, ideate, prototype, and testing. Data were collected through direct observation and interviews with employees involved in document archiving activities. The results of this study are presented in the form of a prototype developed using Figma, featuring key functionalities such as a dashboard, fast document search, document upload, notifications, and role-based access control. Testing results indicate that the proposed UI/UX design is user-friendly, intuitive, and capable of improving work efficiency, although several minor improvements are still required. Therefore, this design is expected to serve as a foundation for the development of an effective digital archiving system and to support digital transformation in the banking sector.